ANALYSIS OF CAPITAL AND CREDIT ASSISTANCE FOR MICRO-BUSINESS GROUPS BY THE SHARIA EMPLOYEE COOPERATIVE OFFICE OF PT. ISKANDAR MUDA FERTILIZER LHOKSEUMAWE CITY - Fadilla Putri Siregar; Darmayanti, Mita; Arjuna Putra, Bambang; Nurrzai, Aziz; Nur Ilham, Rico (PT. Radja Intercontinental Publishing, 2023)
This study aims to analyze loan capital and business volume against residual business results (SHU) with total assets as a moderating variable in the Sharia Employee Cooperative of PT pupuk Iskandar Muda Kota Lhokseumawe. Research Approach using quantitative methods. Quantitative research is a systematic scientific research of parts and phenomena and their relationships. T Type of research uses a type of associative research, which is research carried out to determine the relationship between two or more variables and from the results of this study can be used to build a theory that serves to explain or control a symptom. In taking a sample, the researcher has the criteria used, namely a sample of borrowed capital, business volume, a sample of the remaining business results and a sample of total assets. In this case, the sample used is for the year ended December 31, 2021. The data collection techniques are as follows: 1) Documentation Method, 2) Interview Method. In this interview technique, there is a process of interaction, discussion and presentation. Data analysis techniques are in the form of multiple linear regression analysis (Multiple Linear Regretion Analysis). The results of his research showed that Borrowed capital has an insignificant effect on the Remaining Business Results (SHU) of the Lhokseumawe City